Current Status of the Management of Plant Protection Product Containers in Cho Moi District, An Giang Province, Vietnam - Trung Thanh Nguyen; Son Dai Hai Cao; Quynh Anh Nguyen Thi; Phuoc Toan Phan; Ngoc Thach Tran; Le Ba Tran; Tri Thich Le; Quoc Thao Tran; Nhat Huy Nguyen (Nakhara : Journal of Environmental Design and Planning, 2021)
Every year, thousands of tons of plant protection product (PPP) containers are indiscriminately discharged into the environment as toxic waste that has a negative impact on the land, water, and air environment as well as public health. This study surveyed the use of PPPs in rice cultivation, and the generation of hazardous waste (HW) when using pesticides, specifically pesticide packaging and containers in Long Kien and Long Dien B communes, Cho Moi district, An Giang province, Vietnam. Data collection was conducted through direct interviews, mainly collecting personal information of farmers in the surveyed area, the current situation with regard to pesticide use, container management, environmental awareness, and proposals for hazardous waste management from the farmers’ perspectives. The results show that local farmers are aware of the harmful effects of pesticide containers, but they are not able to make use of effective methods of collecting and treating the waste containers properly. Based on the survey results, several solutions are proposed for managing HW in order to reduce environmental pollution from the use of pesticides, minimize the impacts of HW on people's health, and contribute to local sustainable development.